The sensitivity to polarization in stratospheric aerosol retrievals from limb scattered sunlight measurements. (March 2017) - Elash, B.J.; Bourassa, A.E.; Rieger, L.A.; Dueck, S.R.; Zawada, D.J.; Degenstein, D.A.
Abstract: Satellite measurements of limb scattered sunlight at visible and near infrared wavelengths have been used successfully for several years to retrieve the vertical profile of stratospheric aerosol extinction coefficient. The existing satellite measurements are of the total radiance, with very little knowledge or impact of the polarization state of the limb radiance. Recently proposed instrument concepts for stratospheric aerosol profiling have been designed to measure the linearly polarized radiance. Yet, to date, the impact of the polarized measurement on the retrievals has not been systematically studied. Here we use a fully spherical, multiple scattering radiative transfer model to perform a sensitivity study on the effects of the polarized measurement on stratospheric aerosol extinction retrievals through specific investigations of the aerosol signal fraction in polarized measurements, potential retrieval bias, and achievable precision. In this study, we simulate both total and linearly polarized measurements, for a wide range of limb viewing geometries that are encountered in typical low earth orbits and for various aerosol loading scenarios. The orientation of the linear polarization with respect to the horizon is also studied. Taking into account instrument signal to noise levels it is found that in general, the linear polarization can be used as effectively as the total radiance measurement, with consideration of instrument signal to noise capabilities; however the horizontal polarization is more promising in terms of signal magnitude. Highlights: A study to compare total and polarized radiance measurements effect on aerosol retrievals is presented. No clear advantage to using the linearly polarized measurement for aerosol retrievals. Only disadvantage is the lower signal levels from measuring a polarized radiance. Between polarizations no significant change in the observed bias is observed. Linearly-polarized measurement can be used to achieve approximately equal results.